A Survey on Women's Motivation to Reduce Poverty - Pitaloka, Lola Kurnia; Setiawan, Avi Budi; Alfianti, Ririn (Universitas Negeri Semarang, 2021)
Nowadays, women still become an objectsof life. Even though women can be competent objects of development. Lack of motivation to women is the main problem why women are not productive in public matters. The purpose of this study was to see whether women's empowerment could increase women's motivation to alleviate poverty. This research is an exploratory research which intends to collect facts in depth. The population in this study were 229 women from poor communities who did not or had not worked in Kudus Regency. The sample obtained from Slovin formula is 145 women with the sampling technique using random sampling. Data were collected using a questionnaire and analyzed using SEM with the warpPLS analysis tool. This research shows that the motivation of the population of women does indeed have a significant effect on poverty alleviation because motivation makes what women do to be unbiased. Empowerment of women does not have any effect on motivation for poverty alleviation.